Perbandingan Berbagai Metode Pengamatan Mycobacterium Tuberculosis secara Mikroskopis - Widodo, Widodo; Sugiyatmini, Tri; Purlinda, Devi Etevia (Poltekkes Kemenkes Semarang, 2024)
Technological developments are increasingly rapid in the field of identification and special equipment in the field of microbiology, the development of staining methods and microscopic observation is growing rapidly. The Ziehl Neelsen staining method is still an alternative follow-up to other alternative treatments using the Auramin O staining method with flurocene microscope observation. This research is an analytical observational study and a cross sectional research design to see the differences in readings between Ziehl Neelsen staining, flurocene auramin and gram staining. We used isolates that had been identified as Mycobacterium tuberculosis which we obtained from Balepkes and Pak provinces of Central Java under non-activation conditions, by autoclaving at 121 degrees for 15 minutes. The number of samples was 10 slides with Ziehl Neelsen staining, Flurocene Auramin and Gram staining. The results of the sensitivity and specificity research between Ziehl Neelsen and auramin O were 100%. Meanwhile, the gram staining method and SEM observation cannot be compared because they can only observe bacterial morphology. From the research results it can be concluded that Auramin O can be used as an alternative Ziehl Neelsen painting agent.